KAJIAN ESTETIKA BENTUK PADA FASADE PERUMAHAN REAL ESTATE DI YOGYAKARTA - Suparno Sastra M (Universitas Negeri Yogyakarta, 2016)
Technology in construction and building materials was instrumental in the development of the design andperiodization of architectural style. Particularly in housing, development in the physical infrastructure of housingsuch as real estate building in various housing complexes in Yogyakarta already generated diversity in facadedesign and various types of the arrangement of architectural elements that are very phenomenal. Therefore, thisstudy is so important and necessary to conduct in order to (a) find out the principles of the arrangement ofarchitectural elements in real estate building facade, and (b) describe the identification of the architecturalelements forming a configuration of real estate building façade. The study used an explorative method forexploration on field and made a qualitative analysis to find the facts. Areas of the study include the four residentialreal estate locations in Sleman Regency, Yogyakarta province. The study was conducted in the housings ofGejayan Puri Indah, Casa Grande, Bale Hinggil Residence, and Hyarta Residence. The samples were standardtypebuildings, because it is expected to maximally represent diversity in housing design in the residentiallocations. The unit of analysis was building facades on four residential locations. Parameters of the architecturalelements of the facade were roof, walls, columns, openings, main entrance, terrace and balcony, andornamentation. The arrangement of residential building facade elements was studied on the bases of symmetry,articulation, visual proportion, and horizontal-vertical direction. The results of the study were: first, the symmetry ofa residential building facade shows an asymmetric tendency because of aesthetic considerations and theprinciples of construction as well as the intention to maximize a selling point. Second, all the building facades inthe four residential locations have the strong articulation with focus on main entrance, terrace and balcony, railing,balcony and roof ornamentation as the main elements forming the facade articulation. Third, the visual proportionof facade was found to have more balanced tendency between roof and building body. Fourth, the facades ofresidential buildings have mostly had balanced horizontal-vertical directions because the height of building wasalmost equal to the width of the building and the arrangement of horizontal-vertical architectural elements formingthe facade was averagely composed in a balanced manner.